Development of a bio-nanogate-based electrochemical immunosensing strategy for the detection of anti-hepatitis B surface antigen antibody - Othman, Noor Syamila (2022)
An area requiring real-time analysis is the diagnosis of infectious disease and monitoring of vaccination efficiency against the disease to determine immunity level particularly among high risk group including immunocompromised patients against infectious diseases in screening for immunization program including hepatitis B virus (HBV). However, the conventional methods require laborious work and tedious fabrication of sensing platforms which limit the efficiency in upscaling the screening tests. These further impede the analysis of large cohort of clinical samples. Therefore, an effort is needed in order to improve the outcome of this labbased technology. Generally, a bio-nanogate system involves the use of synthetic or natural molecules as a ‘gate’ towards bioreceptors and ideally, the gating mechanism should respond only upon the presence of external stimuli i.e. targeted analytes in a nanoscale dimension. The versatility of polyamidoamine (PAMAM) dendrimers to form conjugates with proteins can be utilized to form a bio-nanogate. PAMAM interaction with protein bioreceptor and the ability of a bio-nanogate-based immunosensing strategy in detecting an antibody i.e. anti-hepatitis B surface antigen (anti- HBsAg) antibody electrochemically were of interest in this study. An antigenic determinant (aD) region of HBV fused with maltose binding protein (MBP-aD) was synthesized to form a specific bioreceptor for anti- HBsAg antibody in the bio-nanogate system. The bio-nanogate interaction was further analysed for its binding affinity, thermal stability, and thermodynamic analysis. Following that, a proof of concept utilizing displacement immunosensing strategy was conducted electrochemically, where the MBP-aD was immobilized on the screen-printed carbon electrode (SPCE) platform, and further sandwiched with electroconductive PAMAM encapsulated gold nanoparticles (PAMAM-Au), forming the ‘gate’. PAMAM-Au here also functions as a monitoring agent capable of generating a signal response upon a displacement event in the presence of anti-HBsAg antibody in differential pulse voltammetry (DPV) analysis. Finally, the PAMAM-Au displacement efficiency was further improved via implementation of acoustic mixing on modified SPCE platform coupled with piezoelectric transducer. The synthesized MBP-aD was confirmed with western blotting technique. The interaction study revealed that the interaction of MBP-aD with anti- HBsAg antibody has a higher thermal stability and binding affinity (KA = 1.6 x10-5 Lmol-1) as compared to its interaction with PAMAM (KA = 2.9 x 10-6 Lmol-1). Thermodynamic parameters also demonstrated that the bionanogate components interact through van der Waals and hydrogen bonding. Based on the interaction study, it was hypothesized that the interactions among the bio-nanogate components may be able to be manipulated at the nanoscale level for the detection of anti-HBsAg antibody. Under optimal conditions, the hypothesis was proven that the high specificity of anti-HBsAg antibody towards MBP-aD displaced PAMAM-Au, in a range of 1mIU/mL to 1000 mIU/mL with a detection limit (LOD) of 2.5 mIU/mL. The results also showed high specificity and selectivity of the immunosensor platform in detecting anti-HBsAg antibody both in spiked buffer and human serum samples. Furthermore, the incubation/reaction time for detecting anti-HBsAg antibody has been reduced from an initial incubation time of 20 min to 8 min via the improvement of PAMAM-Au displacement efficiency under acoustic streaming effect. The newly developed immunosensor platform utilizing the manipulation of lower interaction between PAMAM-Au (gate) and the candidate bioreceptor (anchor) would ultimately eliminate the need of having specifically designed and labelled analogues which has been commonly used in displacement-based immunoassays.